Human Health Risk Assessment of Toxic Heavy Metals in Commercially Available Rice at Local Markets in Erbil, within the Kurdistan Region of Iraq - Faris Zaidan Jarjees; Dalshad Azeez Darwesh (Zanco Journal of Pure and Applied Sciences, 2024)
For the 15 brands that selected for the present study, a total of 50 rice samples were collected. Including at least 3 samples from each brand were subjected to analysis for the presence of As, Pb, Cd, Ni and Cr using the Inductively Coupled Plasma (ICPE-9820 Shimadzu) technique. Additionally, a survey was conducted to collect information about the rice consumption habits of residents, encompassing the consumed rice types and sources, as well as the rice intake quantity and frequency. The median levels of toxic heavy metals (THMs) in rice were as follows: As (0.607), Pb (0.495), Cd (0.143), Ni (0.346) and Cr (0.162) mg/kg. Factoring in the data on rice consumption, the EDI values (in mg kg/day) were determined for the studied population, resulting in a range of (3.29 x 10-4 – 1.63 x 10-3) for As, (2.38 x 10-4 – 1.18 x 10-3) for Pb, (7.59 x 10-5 – 3.75 x 10-4) for Cd, (1.83 x 10-4 – 9.05 x 10-4) for Ni, and (7.45 x 10-5 – 3.68 x 10-4) for Cr. In the context of non-carcinogenic risk assessment (HQ), all THMs were found to be below the acceptable threshold (= 1), except for As, which exceeded the acceptable level for all age groups. Carcinogenic risk assessment (CR) values for individuals of all ages and genders ranged from 2.03 x 10-6 to 9.08 x 10-3. The average total carcinogenic risk for the population in Erbil was calculated as 5.86 x 10-3. Additionally, males exhibited higher carcinogenic risk levels than females, and individuals in the age group of 11 – 20 faced the highest carcinogenic risk.